The Right to Privacy in International Law: Evolving Standards for Personal Data Protection in the Digital Era - Nafi’ah, Lutfiah Sholikhatun; Prastyanti, Rina Arum (West Science Law and Human Rights, 2025)
Privacy    and    personal    data protection are increasingly important issues in today's  digital  era.  This  article  highlights  the importance    of recognizing    privacy    as    a fundamental    human    right    that    must    be protected   by   the   state   in   accordance   with applicable   human   rights   principles   and   the constitution.   Protection   of   personal   data   is becoming increasingly crucial because it is often a  target  for  irresponsible  parties.  International regulations, such as the Universal Declaration of Human Rights and the General Data Protection Regulation   (GDPR)   in   the   European   Union, provide   a   framework   for   the   protection   of personal data. This article also highlights a key challenge to protecting privacy, namely finding a  balance  between  the  need  for  security  and individual  privacy.  Efforts  such  as  developing specific   laws   on   personal   data   protection, increasing   public   awareness,   and   enhancing international cooperation are urgently needed. Keywords: privacy,    data    protection,    human rights, regulations, challenges.